Peranan Polisi dalam Penanggulangan Tindak Pidana Pelanggaran Lalu – Lintas Diwilayah Hukum Polres Gorontalo - Muhamad Zulkifli Lamatenggo; Marten Bunga; Robby Waluyo Amu (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This research is empirical in nature, involving direct field observations through interviews with authorized police officers of Bone Bolango who are responsible for handling traffic violations. The findings indicate that the role of the police is crucial in fostering traffic order through comprehensive and adaptive approaches. The strategies required by law enforcement to combat traffic violations emphasize the importance of holistic and contextual methods. Effective strategies must integrate strict law enforcement with public legal education and awareness-building, along with the use of modern technologies such as electronic traffic law enforcement (e-TLE) to enhance monitoring and transparency. The proposed recommendations highlight the need to improve the capacity of police personnel in both quantity and quality through continuous training focused on enforcement techniques and humanistic approaches. A more comprehensive approach is necessary, integrating enforcement, education, and community guidance simultaneously. These strategies must be supported by enhanced infrastructure and technology, such as the development of the e-TLE system and the installation of CCTV at high-risk violation points to improve monitoring effectiveness.